2022
DOI: 10.1021/acs.jchemed.1c01023
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry-Based Activities and Games That Engage Students in Learning Atomic Orbitals

Abstract: Atomic orbitals represent an essential construct used to develop chemical bonding models, upon which other more advanced chemistry topics are built. In this article, we share a series of active-learning activities and a gamified approach to develop students' representational competence about atomic orbitals and to engage students in learning the properties of atomic orbitals. These properties are essential for understanding an array of fundamental concepts such as penetration and shielding, relationships such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…BingOrbital is an original chemistry educational gamification design shared by this contribution. The game aims to practice the recognition of atomic orbitals by RDF and isosurface and has been played in the class following an IBL activity about atomic orbitals (Activity 1 in another Activity paper of this journal) as a form of retrieval practice (drawing information from memory rather than relying on existing notes or a textbook). , The game is also intended to promote engagement and bring fun to the classroom. This game is constructed in a format resembling American version of Bingo, hence the portmanteau “BingOrbital”.…”
Section: Bingorbital–chemist’s Version Of the Bingo Gamementioning
confidence: 99%
See 3 more Smart Citations
“…BingOrbital is an original chemistry educational gamification design shared by this contribution. The game aims to practice the recognition of atomic orbitals by RDF and isosurface and has been played in the class following an IBL activity about atomic orbitals (Activity 1 in another Activity paper of this journal) as a form of retrieval practice (drawing information from memory rather than relying on existing notes or a textbook). , The game is also intended to promote engagement and bring fun to the classroom. This game is constructed in a format resembling American version of Bingo, hence the portmanteau “BingOrbital”.…”
Section: Bingorbital–chemist’s Version Of the Bingo Gamementioning
confidence: 99%
“…The Orbital Explorer Web site has been integrated with inquiry-based learning (IBL) activities and has been implemented in the Honors General Chemistry I course at Rutgers University since the Fall 2019 academic term. The IBL activities are described in another publication of this journal and contain two sets of activities: Activity 1 and Activity 2, which are implemented in sequence . Activity 1 focuses on atomic orbital quantum numbers, nodal surfaces, sizes, and energies .…”
Section: Classroom Implementation and Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, IBL has received much attention regarding its effectiveness on students learning outcomes. Many studies have found that IBL enable students to explore, communicate and discover knowledge and gain a deeper understanding of the subject matter (de Dieu Kwitonda et al, 2021;Hofer et al, 2018;Li et al, 2022), increases academic performance (Azizoglu et al, 2022;Bodner & Elmas, 2020;Singh, 2020) and enhance the development of critical thinking and problem-solving skills (Arsal, 2017;Duran & Dokme, 2016;Herawati et al, 2020).…”
Section: Inquiry-based Learningmentioning
confidence: 99%